أثر الاستثمار الأجنبي المباشر على المؤسسات الصغيرة والمتوسطة في الجزائر دراسة قياسية (2001-2022) - ابراهيم, احموده; عبد الرزاق, حتيري; عبدالقادر, احمادي (جامعة الوادي - University of Eloued, 2023)
"تهدف هذه الدراسة إلى إبراز أثر الاستثمار الأجنبي المباشر على المؤسسات الصغيرة والمتوسطة، حيث أن الاستثمار له دور كبير على المؤسسات المحلية في تحقيق التنمية الاقتصادية، وللإجابة على تساؤلات هذه الدراسة تم جمع مجموعة من البيانات والمعلومات التي تعبر الإطار النظري والتطبيقي في الجزائر. تم الاعتماد على المنهج الوصفي بالإضافة الى المنهج التحليلي وصولاً إلى الدراسة القياسية. ولقد توصلنا في هذه الدراسة إلى وجود المعادلة الاقتصادية والإحصائية مقبولة من خلال دراسة متغيرات أثر الاستثمار الأجنبي المباشر على المؤسسات الصغيرة والمتوسطة للفترة (2001-2022) من خلال الاعتماد على إحصائيات البنك الدولي وتقارير وزارة المؤسسات الصغيرة والمتوسطة، كما وصلت الدراسة إلى أن هناك علاقة تكامل مشترك بين متغيرات الدراسة. " "This study aims to highlight the impact of foreign direct investment on small and medium-sized enterprises, as investment has a great role for local enterprises in achieving economic development, and to answer the questions of this study, a set of data and information was collected that express the theoretical and applied framework in Algeria. The descriptive curriculum was adopted in addition to the analytical curriculum to reach the standard study. In this study, we have come to the existence of an acceptable economic and statistical equation by studying the variables of the impact of foreign direct investment on small and medium enterprises for the period (2001-2022) by relying on the statistics of the World Bank and the reports of the Ministry of small and medium enterprises, and the study also reached that there is a common integration relationship between the study variables "
Keywords: استثمار أجنبي مباشر، مؤسسات صغير ومتوسطة، مناخ استثمار.; foreign direct investment, small and medium enterprises, investment climate